Lepanthes vespertina (Orchidaceae: Pleurothallidinae), a new species from Costa Rica - Bogarín, Diego; Rodríguez-Cáceres, Marisol; Ulloa-Vargas, Lisseth (Phytotaxa, 2025)
Lepanthes is the second most diverse orchid genus in Costa Rica, with 165 recorded species, 31.5% of which are endemic. Several new species have recently been described as part of the Flora Costaricensis–Orchidaceae project led by the Lankester Botanical Garden. However, the taxonomy of Lepanthes still presents historical gaps, particularly regarding collections made by botanist A. R. Endrés between 1866 and 1870, some of which remain poorly documented. In this study, we describe and illustrate a new species, Lepanthes vespertina, which is morphologically similar to L. umbonifera, a species originally collected and illustrated by Endrés in 1867 and described by C. Luer in 1995. To confirm the identity of the new species, we conducted field collections in the province of Cartago and reviewed herbarium specimens, digital types, and Endrés’ original illustrations. The new species differs from L. umbonifera by its ruby-colored, obovate petals (vs. cinnabar-red, cuneate petals in L. umbonifera). The labellum is bilaminate, with obovate blades that converge beneath the apex of the column (vs. ovate, straight, and separated blades in L. umbonifera), and it bears a cylindrical, pubescent, and bifid appendix (vs. globose and apiculate). The results clarify some taxonomic uncertainties derived from Endrés’ historical records and demonstrate the importance of incorporating illustrations from old collections into modern taxonomic work.